Digital tools for worker management and psycho-social risks in the workplace: Evidence from the ESENER survey - Cesira Urzí Brancati; Maurizio Curtarelli (European Commission, Joint Research Centre (JRC), 2021)
This article explores the association between digital technologies that enable new forms of man-agement and the presence of psychosocial risks in the workplace, drawing on a representative survey of European establishments (ESENER 2019). It also ascertains whether occupational safety and health (OSH) preventive measures and policies may play a mitigating role in managing risks and reducing the potentially negative impact of technology. In line with the literature and with prior expectations, our analysis reveals that digital technologies enabling the new forms of management are associated to increased psychosocial risks, which in turn can result in work-related stress and other mental health issues. It also confirmed that OSH measures, such as having an action plan to prevent work related stress, help reducing psychosocial risks in the workplace, but do not mitigate the relationship between psychosocial risks and management technologies.
Keywords: 330; algorithmic management; digitalisation; workplace monitoring; psychosocial risks; work related stress